Locating Microseism Sources Using Spurious Arrivals in Intercontinental Noise Correlations. Issue 10 (26th October 2017) - Retailleau, Lise; Boué, Pierre; Stehly, Laurent; Campillo, Michel
Abstract: The accuracy of Green's functions retrieved from seismic noise correlations in the microseism frequency band is limited by the uneven distribution of microseism sources at the surface of the Earth. As a result, correlation functions are often biased as compared to the expected Green's functions, and they can include spurious arrivals. These spurious arrivals are seismic arrivals that are visible on the correlation and do not belong to the theoretical impulse response. In this article, we propose to use Rayleigh wave spurious arrivals detected on correlation functions computed between European and United States seismic stations to locate microseism sources in the Atlantic Ocean. We perform a slant stack on a time distance gather of correlations obtained from an array of stations that comprises a regional deployment and a distant station. The arrival times and the apparent slowness of the spurious arrivals lead to the location of their source, which is obtained through a grid search procedure. We discuss improvements in the location through this methodology as compared to classical back projection of microseism energy. This method is interesting because it only requires an array and a distant station on each side of an ocean, conditions that can be met relatively easily. Key Points: An array analysis method is developed to locate microseism sources in the Atlantic Ocean from correlation functions Strong sources generate spurious arrivals that can be identified in the correlation functions